Sustained Yield-some Views - Pant, M. M. (Indian Forester, 1977)
Regardless of the alleged short cominge of the sustained yield concept the foresters should take comfort in one fact - "it works". The alternatives suggested are not practicable. The main attacks on the principle of sustained yield do not appear to be realistic in the Indian context. For example, admittedly, wood will be replaced for some of today's uses, but because it is renewable, it will be converted into many new products. The total future demand for wood it bound to increase considerably. The available supply of wood, therefore, needs rationing and present yield must be sacrified for future generation. The critics of sustained yield seldom, if ever, analyse the impact that a variable flow of forest products would have on social, economic and ecological factor. (community stability, self reliance, raw meterial security, rights and concessions, externalities, etc.) in the forest management practices. The economic princlples should be given due weight within the framework of the sutained yield model. Depending on the objects of management of the forest, the rotation should be determined using the available economic tools and keeping the constraints in view. Once the rotation is fixed, the area of the annual coupe should be governed by sustained yield. Our main "concern is for Forestry - and fOr economics only for it may serve Our profession.